(untitled) (Research, Society and Development, 2022)
The article aims to analyze whether the creation of the Education Quality Index (IQE) and the Escola Nota 10 Award has repercussions on the school networks of three small municipalities in Ceará: Cariré, Pires Ferreira and Mucambo. The period analyzed is from 2012 to 2018, when these accountability mechanisms were already in place. It is characterized as a qualitative research, descriptive and explanatory and uses multiple case studies. Quantitative data were obtained from the Statistical Synopses of Basic Education, published annually by the National Institute for Educational Studies and Research Anísio Teixeira as a result of the School Census collection, and semi-structured interviews were applied to a group of subjects who work in municipal education in the three networks. It was found that in the three municipalities, the management of the school network has a strong presence of the logic of results in external evaluations with a view to improving the performance of students in Spaece and Saeb and this purpose has led to a set of evaluation actions developed by schools. The infrastructure conditions of municipal schools improved significantly, although the deponents were not able to inform whether the invested resources came from the share of ICMS tax. It was also found that, although the redistribution of the share of ICMS tax in Ceará reaches higher financial values for small municipalities, such as the three studied, the Escola Nota 10 Award is the initiative that makes the results more tangible and visible in the community, having more social repercussions.